Molecular Mechanisms of Chloroquine and Hydroxychloroquine Used in Cancer Therapy - De Sanctis, Juan Bautista; Charris, Jaime; Blanco, Zuleyma; Ramírez, Hegira; Martínez, Gricelis Patricia; Mijares, Michael Rodney (Anti-cancer agents in medicinal chemistry, 2023)
Tumour relapse, chemotherapy resistance, and metastasis continue to be unsolved issues in cancer therapy. A recent approach has been to scrutinise drugs used in the clinic for other illnesses and modify their structure to increase selectivity to cancer cells. Chloroquine (CQ) and hydroxychloroquine (HCQ), known antimalarials, have successfully treated autoimmune and neoplastic diseases. CQ and HCQ, well-known lysosomotropic agents, induce apoptosis, downregulate autophagy, and modify the tumour microenvironment. Moreover, they affect the Toll 9/NF-κB receptor pathway, activate stress response pathways, enhance p53 activity and CXCR4-CXCL12 expression in cancer cells, which would help explain their effects in cancer treatment. These compounds can normalise the tumourassociated vasculature, promote the activation of the immune system, change the phenotype of tumour-associated macrophages (from M2 to M1), and stimulate cancer-associated fibroblasts. We aim to review the historical aspects of CQ and its derivatives and the most relevant mechanisms that support the therapeutic use of CQ and HCQ for the treatment of cancer.
Keywords: Signal Transduction; hydroxychloroquine; metastasis; Antimalarials; Chloroquine; chemotherapy; apoptosis; lidé; non-small cell lung cancer; nádorové mikroprostředí; repurposing drugs in oncology; Tumor Microenvironment; hydroxychlorochin; Hydroxychloroquine; Neoplasm Recurrence, Local; lokální recidiva nádoru; antimalarika; Humans; signální transdukce; chlorochin